2002
DOI: 10.1007/s00134-002-1256-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms of severe respiratory syncytial virus bronchiolitis

Abstract: Respiratory syncytial virus (RSV) bronchiolitis resulting in respiratory insufficiency is frequently encountered during the winter season in paediatric intensive care units. This review evaluates potential determinants described in severe RSV bronchiolitis with special attention to the role of immaturity of immune responses during infancy. Pre-existent cardiac or pulmonary compromises have been documented as clinical risk factors for severe RSV bronchiolitis. In addition to this group of infants with pre-morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 71 publications
2
30
0
1
Order By: Relevance
“…In addition, a recent study performed in mice (Lukacs et al, 2006) shows the different disease characteristics caused by two different strains of RSV-A, A2 and Line 19, independently of virus replication, thus suggesting different RSV pathogenicities within the same antigenic group; (4) patients with bronchiolitis were significantly younger than patients with other lower RTIs. This seems to be largely due to the younger more immature host immune system (Bont and Kimpen, 2002;Marchant and Goldman, 2005;Roman et al, 1997;van Drunen Littel-van den Hurk et al, 2007), which causes an inappropriate shift toward a Th2 immune response to RSV infection, thus resulting in bronchiolitis; (5) symptom duration was significantly longer in patients with bronchiolitis; (6) 7/10 patients examined after discharge still shed virus 20-30 days after onset of symptoms. It remains to be defined if virus persistence in NPA is due to virus' characteristics or to an impaired RSV clearance resulting from an inefficient immune (in particular IgE) response; (7) male sex is independently associated with a higher risk of RSV bronchiolitis (p = 0.018).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, a recent study performed in mice (Lukacs et al, 2006) shows the different disease characteristics caused by two different strains of RSV-A, A2 and Line 19, independently of virus replication, thus suggesting different RSV pathogenicities within the same antigenic group; (4) patients with bronchiolitis were significantly younger than patients with other lower RTIs. This seems to be largely due to the younger more immature host immune system (Bont and Kimpen, 2002;Marchant and Goldman, 2005;Roman et al, 1997;van Drunen Littel-van den Hurk et al, 2007), which causes an inappropriate shift toward a Th2 immune response to RSV infection, thus resulting in bronchiolitis; (5) symptom duration was significantly longer in patients with bronchiolitis; (6) 7/10 patients examined after discharge still shed virus 20-30 days after onset of symptoms. It remains to be defined if virus persistence in NPA is due to virus' characteristics or to an impaired RSV clearance resulting from an inefficient immune (in particular IgE) response; (7) male sex is independently associated with a higher risk of RSV bronchiolitis (p = 0.018).…”
Section: Discussionmentioning
confidence: 93%
“…As the production of Th1 cytokines can be inhibited by cytokines secreted by Th2 lymphocytes, an adequate balance of Th1 and Th2 cytokines is essential for the efficient eradication of RSV. Several studies have shown a correlation between predominant Th2 responses in infants with RSV disease severity (1,12,74). TLR-4 and CD14 have been shown to sense RSV, and TLR-4-deficient mice developed delayed clearance of RSV as well as a predominant Th2 response which correlated with disease progression (29,92).…”
Section: Ebv Ebv Infection Occurring In Early Childhood Is Usually Nmentioning
confidence: 99%
“…4 Previous infections do not prevent reinfections, because a proliferative booster response by RSV-specific memory T cells is not induced. 5 As a result, repeated infections with RSV are common in all age groups. RSV causes about 70% of viral bronchiolitis cases, and recurrent wheeze is frequent in children after recovery.…”
mentioning
confidence: 99%